Uneven Impact of Covid-19 on Sex Workers in Spain - Carmen Meneses-Falcón; Antonio Rúa-Vieites; Olaya García-Vázquez (Feminismo/s)
The coronavirus pandemic has had major impacts on sex workers, with notable differences in bargaining power, coercion, and health. Therefore, the aim of this research is to describe the different impacts of the Covid-19 pandemic on paid sex workers. For this purpose, we conducted a comparative analysis using questionnaires collected from 605 individuals representing two segments of sex industry: one socio-economically lower (415) and the other middle-income (190). In both cases, a sociological questionnaire was used. In S1, it was conducted in person with intentional sampling, while in S2, it was conducted online using social media. Regarding the results, there were significant differences between the two groups, with the lower segment being more vulnerable and facing worse conditions: more difficulties with their documents, lower level of education, less support network, more clients, more insecurity in the place where they work (streets, industrial estates or roads), younger age of starting prostitution, more coercion or need to start (most reported reasons to start in prostitution were economic need, lack of documentation, family responsibilities and debts), less possibilities of health insurance, worse physical and mental health, more food insecurity, and lower income. The middle sector showed: more autonomy, was less impacted by the Covid-19 pandemic, had been in Spain for longer, often holding a residence permit, having more protection measures, having a higher level of education, having a greater support network, having started prostitution at an older age, and were less likely to have been coerced into it. In conclusion, it is important not to homogenise all people in sex work, as there are different sectors and needs within the sex market in Spain, which require different or more targeted policies and interventions.